How and when team reflexivity influences employee innovative behavior. Issue 1 (8th July 2021) - Wang, Zhining; Cui, Tao; Cai, Shaohan
Abstract : Purpose: Based on affective events theory, this study explores the cross-level effect of team reflexivity on employee innovative behaviors. Specifically, the authors examine the mediating effects of affective and normative commitment on this relationship, as well as the moderating effects of benevolent leadership. Design/methodology/approach: The authors surveyed 341 employees and their direct supervisors in 74 work units and utilized multilevel path analysis to test a model of cross-level moderated mediation. Findings: The study analysis results suggest that team reflexivity significantly contributes to employee innovative behavior. Both affective commitment and normative commitment mediate this relationship. Benevolent leadership not only enhances the relationship between team reflexivity and affective/normative commitment, but also reinforces the linkage of team reflexivity→affective commitment→employee innovative behavior. Practical implications: The current study suggests that organizations should invest more in promoting team reflexivity and benevolent leadership in workplace. Furthermore, managers need to develop appropriate employees training programs and pay more attention to employees' work and personal lives. They need to make efforts to enhance employees' affective and normative commitment, thereby facilitating their innovative behavior. Originality/value: This research identifies affective commitment and normative commitment as key mediators that link team reflexivity to employee innovative behavior and reveals the moderating role of benevolent leadership in the process.